Análisis socioeconómico del trabajo doméstico remunerado en el barrio Centenario en la parroquia Ximena del cantón Guayaquil provincia del Guayas - Alvarado García, Diana Rebeca (2018)
The objective of the research is to analyze the socioeconomic situation of paid domestic workers in Barrio Central in the parish of Ximena del Cantón Guayaquil, Province of Guayas, during the last years, they have been one of the most vulnerable sectors, due to their labor rights they were not completed, the year 2008 is issued to the LAW OF COMPULSORY AFFILIATION where people are already talking about lending attention to the law of Ecuadorian citizenship. For what I have been able to carry out the investigation through interviews and surveys to verify the fulfillment of those previously sent by the Ecuadorian State, whether it has been favorable or not for them.......